Substructure searching, similarity calculations and fingerprints - Rijnbeek, Mark (Henry Stewart Talks, 2011)
Searching chemical compounds in data sets, Querying for a fragment (substructure), Similarity to the query input, Algorithms and performance aspects, Concept of fingerprinting, Use of fingerprinting for searching data sets